Analysis of Customer’s Continuous Use of Maritime Transportation Mobile Ticketing Application - Anggraini, Adeilla Rahmi; Windasari, Nila Armelia (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
With the rise of smartphones and internet connectivity, travellers have been increasingly seeking quicker and smoother purchasing processes. To address this behaviour, a passenger shipping company, launched their mobile ticketing app in 2018. However, despite closing offline ticketing booths in late 2023, the app adoption remains low. This research investigates factors influencing user adoption and usage of the app, employing a modified UTAUT model. A mixed-method approach utilizes questionnaires, data analysis using SPSS and PLS-SEM, and cluster analysis to identify user segments and pain points. The research analysis finds that only performance expectancy, social influence, voluntariness of use, system quality, and system quality with a moderating variable frequency of app use impact the user’s intention to continue using the app. These results are further clustered into four categories based on the DOI theory. These findings can be used by the company and other maritime transportation companies seeking to leverage mobile technology for improved customer experience and ticketing efficiency.